2019
DOI: 10.18203/2349-3291.ijcp20192025
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality pattern of very low birth weight and extremely low birth weight neonates in a tertiary care hospital

Abstract: Background: Although the mortality and morbidity rates for Very Low Birth Weight (VLBW) and Extremely Low Birth Weight (ELBW) neonates have improved over last few decades, they still remain highly vulnerable groups. This study determines the neonatal morbidity and mortality within first four weeks of life in VLBW and ELBW neonates.Methods: It was a hospital based prospective study conducted in the department of paediatrics at GB Pant hospital, an associated hospital of Government Medical College Srinagar. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, a previous study has shown that low birth weight occurs due to the interplay of many factors. 5 Maternal age is an important variable that causes LBW and premature birth of babies. 6 However, several studies stated that maternal age is not a significant factor influencing newborn weight, while reported that the very young age of the mother is a causal cause of the increased risk of LBW and premature babies 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a previous study has shown that low birth weight occurs due to the interplay of many factors. 5 Maternal age is an important variable that causes LBW and premature birth of babies. 6 However, several studies stated that maternal age is not a significant factor influencing newborn weight, while reported that the very young age of the mother is a causal cause of the increased risk of LBW and premature babies 7 .…”
Section: Introductionmentioning
confidence: 99%